THE IMPLEMENTATION OF MITIGATION POLICY OF SIDOARJO MUDFLOW - Suwondo Putro, Prasojo Bayu (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: The Implementation of Mitigation Policy of Sidoarjo Mudflow. On May 29, 2006, a large-scale mudflow eruption was caused by a technical error during an oil exploration in the Sidoarjo District of the East Java province of Indonesia. The mudflow spread widely, encompassing 12 villages and forcing around 40,000 people to relocate. The mudflow is still spreading, and will continue to do so for the next 30 years. We must learn more from the mitigation policy that were implemented in order to design better policy models for future actions. This paper presents the policy implementation analysis on the mudflow disaster mitigation. We using qualitative research methods, and applying Edward III model as the analyzing tool of implementation process. The research finding is the Indonesian Government should carry out policy formulation in the form of "Act concerning Mitigation of Natural Phenomenon Impact that affects the Livelihood of the People." This Act is expected to be the solution of the private and legal issues arising from the impact of Sidoarjo mudflow, as a non-catastrophic natural phenomenon and for other natural phenomenons that would be emerged as well. Hence, the recovery of environment, social, economic and infrastructure sectors can be done more quickly along with the efforts to prevent the spreading of mud until it stops. Keywords: Sidoarjo Mudflow, Presidential Regulation, BPLS, Disaster Â  Abstrak: Implementasi Kebijakan Mitigasi Lumpur Sidoarjo. Pada tanggal 29 Mei 2006, sebuah ledakan lumpur skala besar yang disebabkan oleh kesalahan teknik pada proses pengeboran minyak terjadi di Kabupaten Sidoarjo, Provinsi Jawa Timur, Indonesia. Lumpur tersebut meluap luas yang menyebabkan 12 desa tergenang dan setidaknya 40.000 orang terpaksa berpindah. Sampai saat ini luapan lumpur masih terjadi dan akan terus terjadi sampai 30 tahun mendatang. Studi ini menyajikan analisa dari pelaksanaan kebijakan atas mitigasi bencana lumpur, dengan metode kualitatif dan menerapkan model dari Edward III sebagai alat analisa pada proses implementasi kebijakan. Hasil riset ini, Pemerintah Republik Indonesia harus menyusun Undang-Undang terkait Mitigasi atas Dampak Fenomena Alam yang berdampak terhadap Kehidupan Masyarakat. Kedepan UU ini dapat menjadi solusi bagi permasalahan yang timbul akibat dari dampak lumpur Sidoarjo yang dianggap sebagai fenomena alam non bencana serta bagi fenomena alam lain. Sehingga, pemulihan akibat dampak pada sektor lingkungan, sosial, ekonomi dan infrastruktur dapat dilaksanakan secepatnya. Kata Kunci: Lumpur Sidoarjo, Peraturan Presiden, BPLS, Bencana